Systematic Review on Peri-Operative Intravenous Fluid: ‘Restrictive vs Liberal’ Fluid use on Major Abdominal Surgical Patients - Waine, Arnold; Kevau, Ikau; Samof, Lucas; Taufa, Shalon (International Journal of Anesthesia, 2025)
Background Intravenous Fluids use during surgery is a common practice for many reasons. However recent evaluation of perioperative abdominal surgery patients have poised many issues. Mostly on the type of fluid and quantity of volume usage on major abdominal surgery. Many studies into this aspect of perioperative fluid usage have been done, and volume definition have been accrued either restrictive (Maintenance fluid of less than 1.75 Liters) or liberal or standard (Maintenance fluid between 1.75 Liters to 2.75 Liters) usage. The outcome was assessed to ascertain the best patient recovery without complications from the two fluid regime. Result/Discussion After PRISMA exclusion criteria, there were eight randomized control studies assessed to provide a summary, comparing all the studies using either restrictive fluid or liberal fluids used in major abdominal surgery. Post operative complications and the length of hospital stay were assessed as the major outcomes end points and the cumulative result favored those with restrictive fluid usage. Conclusion Although the restrictive use of fluids in abdominal surgery is favored from the measured outcomes, there are inherent cofounders and heterogenicity in the eight studies that require more detail studies involving multiple study centers and population.
Keywords: Intravenous fluid; abdominal surgical patients; neurotransmitter